Selective serotonin reuptake inhibitors: meta-analysis of efficacy and acceptability. Issue 6879 (13th March 1993) - Song, F; Freemantle, N; Sheldon, T A; House, A; Watson, P; Long, A; Mason, J
Abstract : OBJECTIVE–To examine the evidence for using selective serotonin reuptake inhibitors instead of tricyclic antidepressants in the first line treatment of depression. DESIGN–Meta-analysis of 63 randomised controlled trials comparing the efficacy and acceptability of selective serotonin reuptake inhibitors with those of tricyclic and related antidepressants. MAIN OUTCOME MEASURES–Improvement in mean scores on Hamilton depression rating scale for 53 randomised controlled trials. Pooled drop out rates from the 58 trials which reported drop out by treatment group. RESULTS–Among the 20 studies reporting standard deviation for the Hamilton score no difference was found in efficacy between serotonin reuptake inhibitors and tricyclic and related antidepressants (standardised mean difference 0.004, 95% confidence interval -0.096 to 0.105). The difference remained insignificant when the remaining 33 studies that used the 17 item and 21 item Hamilton score were included by ascribing weighted standard deviations. The odds ratio for drop out rate in patients receiving serotonin reuptake inhibitors compared with those receiving tricyclic antidepressants was 0.95 (0.86 to 1.07). Similar proportions in both groups cited lack of efficacy as the reason for dropping out but slightly more patients in the tricyclic group cited side effects (18.8% v 15.4% in serotonin reuptake group). CONCLUSIONS–Routine use of selective serotonin reuptake inhibitors as the first line treatment of depressive illness may greatly increase cost with only questionable benefit.